THE ROLE OF SOCIAL CAPITAL IN DISASTER MANAGEMENT OF DISASTER VULNERABLE VILLAGE COMMUNITY ON THE MERAPI ERUPTION - Entoh Tohani; Lutfi Wibawa (LPMPP Universitas Negeri Yogyakarta, 2019)
Community resilience to anticipate disaster depends on the possession of social capital that grows in the community. Social capital can produce positive effects, unfortunately, disaster mitigations have been dominated by the development of human capital skills than social capital skills. This study aims to determine the role of social capital in disaster management in the disaster vulnerable communities of the Merapi Mount, taking a case in Girikerto village, Turi Sub-district, Sleman Regency, Special Province of Yogyakarta, Indonesia as one area with high risk of the eruption. Independent interviews and focused group discussions were done involving hamlet heads, village government officials, and members of community disaster organizations; in addition to observation in the village dailylife. The results showed that social capital covering values and norms, commitment, trust, networking and sharing of information or knowledge provides benefits in the form of increased community awareness of disaster, social solidarity, and disaster knowledge of the citizens. Therefore, it is important to held community empowerment using an educational approach that is based on the utilization of social capital directly and planned in disaster vulnerable areas for enlarging the resiliency capacity of community.